Mitigasi Bencana Sebagai Bahan Pembelajaran IPA dan IPS pada Kurikulum 2013 untuk Jenjang Pendidikan Dasar Kelas 5 - Indarti Komala Dewi; Elly Sukmanasa (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The aims of the research are: a) analyzing the basic competences of natural and social sciences subjects which are relevant to the learning of disaster mitigation; b) analyzing the theme that can be added by the material of disaster mitigation through the subjects of natural and social sciences. The research employed the approach of descriptive qualitative with the method of expert judgment. The analysis of basic competences of natural and social sciences subjects employed the criteria of objective and target of the learning of disaster mitigation, while theme analysis used the technique of Multi Criteria Analysis (MCA). The analysis was done to the teacher book from theme 1 until theme 9. The research result shows that the K3 and K4 of natural science subject there are 3 basic competences, which are 3.3; 3.5 and 4.7 while for social science subject there are also 3 basic competences, which are 3.3; 4.3; and 4.5 and those are relevant with the learning of disaster mitigation. It also shows that the themes of 9, 2,1 and 4 can be added by the material of disaster mitigation. Therefore, it can be inferred that the materials of natural and social sciences can be added by the material of disaster mitigation in the themes mentioned above using the chosen basic competencies.